Numerical model of heat transfer characteristics for sintered-grooved wick heat pipes under non-uniform heat loads - Thanwit Naemsai (2019)
© 2018 Elsevier Ltd A sintered-grooved wick heat pipe, which is a passive two-phase heat transfer device, is widely used in the thermal control and electronic cooling system inside laptops because of its high thermal performance. These devices are mainly confronted with non-uniform heating and cooling loads during operation. In this study, the development of a numerical model for the sintered-grooved wick heat pipe operation was conducted to predict thermal resistance under non-uniform conditions for approaching the real heat transfer mechanism of the heat pipe thermal module. Finite element analysis (FEA) was used to develop the numerical model of the heat pipe. In the model, the non-Darcian transport and convection–diffusion equations were used for the wick region, while the capillary pressure model was used for the vapor–liquid interface. The FEA model was verified with experimental data, which found that the model formulation was in good agreement with the experimental results of the temperature profiles at both the top and bottom of the heat pipe walls. A quantitative comparison was also carried out, which showed that the predicted wall temperatures and thermal resistances deviated from the corresponding experimental data by an average of 4.25% and 3.63%, respectively. Thus, this developed model can provide adequate predictions for heat transfer in order to design a sintered-groove wick heat pipe system.